Headshot of Bobby Woods
Caption on verso reads: "Bobby Woods" Digitization possible through funding from Young Canada Works grant for the summer of 2018. We acknowledge the financial support of the Government of Canada. Nous reconnaissons l'appui financier du gouvernement du Canada.